The Uptake Of Wildlife Research In Botswana: A Study Of Productive Interactions - Morrison, Monica (My University, 2021)
This study set out to identify and understand whether research carried out in or about Botswana Botswana has been focused on producing useful and used work in the area of wildlife and related natural resources, with a view to improving the management of these resources. The study investigated this by examining the interactions of researchers and stakeholders engaged in the management, conservation, and use of wildlife resources in northern Botswana. This work draws on the idea that broader societal impact of research can be estimated by following interactions of researchers with potential users of their research throughout the research process. This approach, based on the idea of productive interactions, acknowledges the difficulty of attributing the uptake, use, and impacts of research findings, and moves the focus of investigation from outcomes at the end point of investigation to all the stages and processes of research. Interactions of researchers with potential users of the research - its stakeholders - increase the likelihood of research findings being put to use. In the thesis, this process is viewed through the concept of an extended community of practice that demonstrates mutual engagement, joint enterprise, and shared repertoire. The study used a mixed methods case study approach including literature review, surveys of principal investigators working under Government of Botswana permits and audience members of a public outreach event, interviews, analysis of document content and bibliographic records, and ad hoc participant observation to establish patterns of interaction among researchers and stakeholders working in northern Botswana, and to investigate perceptions of research use. The study found that the northern Botswana's research community of practice consists of a strong core of researchers based in academic institutions and Non-Governmental Organisations (NGOs) who interact with more loosely connected members of the private sector and several levels of government, and with local community members. Findings included that researchers who engage with non-academic stakeholders outside the inner core of this community of practice at early stages, and throughout the research process, are more likely to see their research applied. Their success also appears to be linked to their commitment to working longer-term in northern Botswana, which allows for more, and deeper, interactions with stakeholders. Findings of this study point to validation of the concept of productive interactions in a local community of practice, with effects that extend beyond Botswana and southern Africa. While productive interactions are already taking place in this community, many of them brokered by NGOs, increased deliberate incorporation of the productive interactions approach into the practice of government managers, researchers, and the tourism private sector is likely to increase the relevance, awareness, and uptake of the resulting findings, and to build trust and understanding among research stakeholders.
Related resources: - https://doi.org/10.6084/m9.figshare.14392991 - https://doi.org/10.6084/m9.figshare.14392988 - https://doi.org/10.6084/m9.figshare.14393177 - https://doi.org/10.6084/m9.figshare.14393225
Keywords: Communities of practice; Conservation science; Research permits